Market competition and demand for skills in a credence goods market: Evidence from face-to-face and web-based non-physician clinician training in rural China - Yi, Hongmei (PLoS One, 2020)
BACKGROUND: Non-physician clinicians (NPCs) providing services in functionally private markets account for a large share of the workforce in the primary care system in many low-income and middle-income countries. Although regular in-service training is believed to be crucial to updating NPCs’ professional knowledge, skills, and practices, participation rates are often low. Low participation may result from the “credence good” nature of the market for primary care: if patients are unable to observe quality improvements from training, NPCs have weaker incentives to participate. Empirical evidence is limited on the relationship between market competition and NPC participation in-service training as well as how participation varies with the type of training available. METHODS: The study uses a dataset of 301 NPCs from three prefectures in Yunnan, a province in southwest China, collected in July 2017. Logistic regression is used to estimate the relationship between competition and NPC’s participation in in-service training. We assess the relationship between participation and both the quantity of competition (number of competitors in the same village and surrounding villages) and the quality of competition (proxied using characteristics of competing clinicians). RESULTS: In 2016, nearly two thirds of NPCs participated in face-to-face or web-based in-service trainings at least once. Specifically, 58 percent of NPCs participated in face-to-face in-service trainings, and 24 percent of NPCs participated in web-based in-service trainings. The quantity of competitors is unrelated to participation in in-service training. The quality of competition is not related to face-to-face training but has a significant positive relationship with participation in web-based training. CONCLUSIONS: Web-based trainings may be a better approach to increase NPC skills in developing country primary care markets.